Kekhasan Moral Kristiani: Ideologis atau Epistemologis? - Joannes haryatmoko (Jurnal Orientasi Baru, 2009)
Does Christian ethics propose an original moral which is different from other ethics? The golden rule could be the starting point of the search for the uniqueness of the christian ethics. Treat others as you would like them to treat you. So treat others as a goal and not as a means. This golden rule still supposes a reciprocal relationship. So it must be viewed in a new perspective which is of generosity. So the categorical imperative must be completed by love your enemies and do good, and lend without any hope of return (Luke 6:35). This completion characterizes the logic of generosity which can be claimed is the uniqueness of christian ethics because it transcends the mere logic of eciprocity of the golden rule. The logic of generosity purifies the christian ethics rom all kinds of interests and expectations. This radicality of following Jesus hrist answers the perplexity of Derrida putting into question of the existence of a sincere gift and pardon. Derridas deconstruction confirms mediately the niqueness of christian ethics. Christianism places ethics in a concrete community with all its organizations, traditions, rites, institutions, theologies and the individuals of its members.